2009
DOI: 10.1111/j.1553-2712.2009.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Serious Bacterial Infections in Febrile Outpatient Pediatric Heart Transplant Recipients

Abstract: Objectives: The purpose of this study was to describe the incidence of serious bacterial infections (SBIs) in febrile outpatient pediatric heart transplant recipients and to assess the utility of using white blood cell (WBC) indices to identify patients at low risk for bacteremia.Methods: A retrospective study was conducted on all heart transplant recipients followed at a single children's hospital. All outpatient visits from January 1, 1995, to June 1, 2007, in which fever was evaluated were reviewed. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first major study to comprehensively describe CRP values among renal transplant patients with suspected infection. Accordingly, a low sensitivity of WBC and ANC in detecting bacterial infections was previously reported in liver and heart transplant recipients . Therefore, despite its limited specificity, CRP concentration may help to rule out bacterial infection and therefore should be included in the laboratory work‐up of patients presenting with fever after solid organ transplantation.…”
Section: Discussionmentioning
confidence: 87%
“…To the best of our knowledge, this is the first major study to comprehensively describe CRP values among renal transplant patients with suspected infection. Accordingly, a low sensitivity of WBC and ANC in detecting bacterial infections was previously reported in liver and heart transplant recipients . Therefore, despite its limited specificity, CRP concentration may help to rule out bacterial infection and therefore should be included in the laboratory work‐up of patients presenting with fever after solid organ transplantation.…”
Section: Discussionmentioning
confidence: 87%
“…In their report, the initial WBC count obtained in the emergency department was low or normal in 71% of patients diagnosed with serious infections (12). Yin et al (13), who described 238 fever episodes in outpatient pediatric heart transplant recipients, assessed the effectiveness of using WBC indices to identify patients at low risk for bacteremia, and similarly found that the WBC count failed to identify all bacteremic cases.…”
Section: Discussionmentioning
confidence: 99%